Effects of recurrent summer droughts on arbuscular mycorrhizal and total fungal communities in experimental grasslands differing in plant diversity and community composition - Albracht, Cynthia; Eisenhauer, Nico; Vogel, Anja; Wagg, Cameron; Buscot, François; Heintz-Buschart, Anna (Frontiers in Soil Science, 2023)
Biodiversity loss and climate change have been determined as major global drivers affecting ecosystems and their functioning. Drought was shown to have negative effects on ecosystems, which could be buffered in more biodiverse systems. Many studies focus on effects on aboveground communities of single drought events, while dynamics of soil-borne communities are still widely unclear, despite their important roles in ecosystem functioning. To elucidate the effect of recurrent summer drought periods on fungal communities in a longterm grassland biodiversity experiment, roof shelters were installed on grassland plots ranging in plant species richness from 1 to 16 and plant functional group richness (1-4 groups). After 9 years of summer droughts, bulk soil was sampled and used for Illumina sequencing of the ITS2 and SSU genes to characterize the total fungal and arbuscular mycorrhizal fungal (AMF) communities, respectively. We found shifts of AMF and total fungi community structures caused by recurrent drought and plant species richness, but no buffering of drought effects by plant diversity. Alpha-diversity (VT or ASV richness) of both AMF and total fungi increased with plant species richness but was not significantly affected by drought. Even though drought overall had minimal long-lasting effects, we found Diversispora and Paraglomus to be more abundant after the drought treatment. AMF communities were affected by the presence of individual plant functional groups, reacting stronger to presence of legumes under drought, while total fungal interaction with plant communities were similar under drought as control. AMF α-diversity differed between plant functional groups in control conditions but was independent of plant community composition under drought. In contrast, total fungi α-diversity was increased by presence of herbs and legumes only under drought. We conclude that recurring moderate summer droughts do not strongly affect soil fungal communities. All shifts can be explained by indirect effects through the plant community and its top-down effect on soils altered by drought. AMF are not less affected than total fungal communities, but rather respond differently by interacting more strongly with legumes in response to drought. Consequently, not plant species richness, but plant functional composition, dominates in shaping fungal communities under recurrent droughts.